Políticas públicas educacionais: a reestruturação produtiva do capital e o pacto pela educação em Catalão Goiás - (:unkn) unknown (Universidade Federal de Goiás, 2015)
The dissertation whose theme is " Public Educational Policies: productive restructuring of capital and the Education Pact in Catalão-Goiás”, justified the choice in reason of practice experiences this research, of teaching and performance in the union in the state public context before and during the implementation of “Education Pact”. Besides, the theme suits characteristics of search line Labor and Social Movements of Strictu Sensu Master's Degree Program of the Federal University of Goiás/Regional Catalão. The main objective of the research is to identify and understand the changes occurred in the world of work in capitalist society. As a function of productive restructuring of capital focusing on coping of Union of Workers in Goiás Education (UWGO), from Public Policy Education implemented by the government of Goiás in 2011, called “Education Pact: a better future requires changes”. Which is based on five pillars: 1) enhance and strengthen the professional education; 2) adopt teaching practices with high impact in student learning; 3) significantly reduce the educational inequality; 4) structure recognition system and merit pay; and 5) perform thorough reform in the management and infrastructure of the state school system. Pillars that were be analyzed during the research, including issues such as: What changes have occurred in the educational context from Education Pact? How relations did territorialize between the governor and the workers by the state public of teaching and the Union of Workers in Goiás Education (UWGO). To systematize these and other questions about the chosen subject, authors and works that deal with the subject were used, to achieve a theoretical foundation, as regards the literature, interviews and structured questionnaires to conduct field research, involving teachers from the state public school by Catalão-GO. In the field research were realized 7 (seven) interviews and answered 30 (thirty) questionnaires by education workers of the state public school by Catalão-GO. In research of additional sources were made queries the available data on the websites of SINTEGO (UWGO) and State Department of Education (SEDUC). Besides, thirty (30) visits to state public schools to examine the infrastructure of these school units.
Educational public policies: the productive restructuring of capital and the education pact in Catalão Goiás
Keywords: Políticas públicas; Trabalho docente; Neoliberalismo; Sindicato; Precarização; Public policy; Teaching work; Neoliberalism; Union; Precariousness; CIENCIAS HUMANAS::GEOGRAFIA